Method and device for judging selectivity of gas separation membrane by adopting dielectric spectrum
The selectivity of the two-dimensional gas separation membrane is judged through the dielectric spectrum method, which solves the problem of difficulty in predicting the selectivity of the two-dimensional gas separation membrane in the prior art, and realizes accurate prediction of the selectivity of CO2 in the CO2/N2 mixed gas, saving research resources.
Patent Information
- Application Number
- CN202311427101.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, it is difficult to accurately predict the selectivity of a two-dimensional gas separation membrane for a specific gas (such as CO2), which causes researchers to spend a lot of time and resources on screening conditions, and resources will be wasted when the screening results are invalid.
The dielectric spectrum method is used to judge the selectivity of the gas separation membrane. By measuring the dielectric relaxation frequency and time of the two-dimensional gas separation membrane under different relative air humidity, the dielectric relaxation time is calculated, and the selectivity of CO2 in the CO2/N2 mixed gas is then judged.
Accurate prediction of CO2 selectivity in CO2/N2 mixed gases under different humidity conditions is achieved, which saves research time and cost, and provides technical support for the design of efficient CO2 selective separation membranes.
Smart Images

Figure CN119915871A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane separation, and more specifically, relates to a method and a device for judging the selectivity of a gas separation membrane by using dielectric spectrum. Background Art
[0002] The development of efficient CO2 separation technology is of great significance in tail gas treatment, natural gas purification and carbon capture. As a purely physical process, membrane separation is regarded as an energy-saving and environmentally friendly technology because it does not involve phase change. However, due to the game effect between the permeability and selectivity of membrane separation, it is crucial to select appropriate membrane materials and operating conditions. The emergence of two-dimensional materials with ultrafast mass transfer and highly ordered molecular channels provides a feasible path to break the game effect of permeability and selectivity faced by traditional membrane separation. Some researchers have observed the enhancing effect of humidity on CO2 separation in many two-dimensional membranes, while in other traditional polymer or mixed matrix membranes, water has a negative effect on the CO2 separation process. The existing technology has not yet revealed how humidity affects the selectivity of CO2 separation membranes.
[0003] It is reported in the prior art that some two-dimensional gas separation membranes can obtain high selectivity for specific gases (such as CO2) under specific conditions. However, the selectivity of the two-dimensional gas separation membrane for the specific gas (such as CO2) is affected by many factors such as interlayer spacing, membrane thickness and temperature. Before the two-dimensional gas separation membrane is actually used to selectively separate gases, it is impossible to accurately predict the selectivity of the two-dimensional gas separation membrane for the specific gas (such as CO2). This requires researchers to spend a lot of experiments to screen conditions, such as humidity, temperature, gas partial pressure, etc., before confirming whether the two-dimensional gas separation membrane has high selectivity for the specific gas (such as CO2). When the optimal conditions are screened, once the selectivity of the two-dimensional gas separation membrane for the specific gas (such as CO2) is not substantially improved, the aforementioned screening work will all become invalid work, wasting the time, energy and economic cost invested by the researchers in this subject.
[0004] To reduce this waste of time, energy and economic costs, researchers are exploring methods to predict the selectivity of two-dimensional membrane separations for specific gases (such as CO2).
[0005] Therefore, there is an urgent need in this field for a method to effectively predict / judge the selectivity of two-dimensional gas separation membranes for specific gases (such as CO2), which can accurately and objectively judge the selectivity of two-dimensional gas separation membranes for specific gases (such as CO2) and save research time and costs. Summary of the invention
[0006] 1. Problem to be solved
[0007] In view of the problem that the selectivity of existing gas separation membranes is difficult to predict, the present invention provides a method for judging the selectivity of gas separation membranes using dielectric spectroscopy;
[0008] Furthermore, the present invention provides a device for judging the selectivity of a gas separation membrane using dielectric spectroscopy, for implementing the above method.
[0009] 2. Technical solution
[0010] In order to solve the above problems, in the present invention, we use layered double hydroxide (LDH) as a model material for CO2 separation, and for the first time use dielectric spectroscopy to study the relaxation state of confined water in a two-dimensional confined space to understand the dependence of two-dimensional membrane gas separation on humidity. The changes in the dielectric spectral signal presented by confined water provide important information about the dielectric environment during gas transmission, thus becoming an important indicator for evaluating CO2 permeation dynamics. In addition, optimizing gas separation performance by adjusting confined water also provides a favorable direction for the rational design of efficient CO2 selective separation membranes based on two-dimensional materials.
[0011] The first aspect of the present invention provides a method for determining the selectivity of a gas separation membrane using dielectric spectroscopy.
[0012] The gas separation membrane includes a two-dimensional gas separation membrane;
[0013] The selectivity includes the selectivity of CO2 in the CO2 / N2 mixed gas; wherein the CO2 / N2 mixed gas refers to a mixed gas containing both CO2 and N2, and is not limited to a mixed gas containing only CO2 and N2;
[0014] Methods include:
[0015] S1 measures the dielectric spectrum of the two-dimensional gas separation membrane in the range of 0.01 to 5 MHz under different relative air humidities, obtains the dielectric relaxation frequency, and then calculates the dielectric relaxation time; the dielectric relaxation frequency is obtained by fitting the dielectric spectrum curve with the Havriliak-Negami equation; the Havriliak-Negami equation is:
[0016]
[0017] Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite frequency ε ∞ The difference between them; τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, ranging from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes;
[0018] S2 determines the selectivity of CO2 in CO2 / N2 mixed gas of two-dimensional gas separation membrane under different relative air humidity according to the size of dielectric relaxation time of two-dimensional gas separation membrane under different relative air humidity:
[0019] The two-dimensional gas separation membrane under any relative air humidity is used as a reference membrane, and the dielectric relaxation time of the reference membrane is τ0; the two-dimensional gas separation membrane under other relative air humidity is used as the two-dimensional gas separation membrane to be tested, and the dielectric relaxation time of the two-dimensional gas separation membrane to be tested is τ;
[0020] When the τ value is greater than τ0, it is judged that the selectivity of the two-dimensional gas separation membrane to CO2 in the CO2 / N2 mixed gas is greater than that of the reference membrane;
[0021] When the τ value is less than τ0, it is judged that the selectivity of the two-dimensional gas separation membrane to CO2 in the CO2 / N2 mixed gas is less than that of the reference membrane.
[0022] In the present invention, the selectivity of CO2 refers to the separation factor obtained by dividing the CO2 / N2 molar ratio on the permeate side (after membrane separation) by the CO2 / N2 molar ratio in the raw gas (before membrane separation) when a CO2 / N2 mixed gas is separated using a gas separation membrane; the CO2 / N2 molar ratio can be obtained by gas chromatography.
[0023] In the present invention, the correlation between the selectivity of CO2 in a CO2 / N2 mixed gas and the dielectric relaxation of a gas separation membrane is discovered for the first time; specifically, for the same gas separation membrane, when the relative air humidity is greater, the characteristic dielectric relaxation time τ value of the gas separation membrane is greater, and the selectivity of the gas separation membrane for separating CO2 in a CO2 / N2 mixed gas is also greater (higher); when the relative air humidity is smaller, the characteristic dielectric relaxation time τ value of the gas separation membrane is smaller, and the selectivity of the gas separation membrane for separating CO2 in a CO2 / N2 mixed gas is also smaller (lower). Therefore, by using the dielectric spectrum test method, the selectivity of the gas separation membrane for separating CO2 in a CO2 / N2 mixed gas under different humidity conditions can be accurately determined.
[0024] A two-dimensional gas separation membrane refers to a membrane having a gas separation function and made of a two-dimensional material having a layered structure. As a preferred embodiment of any technical solution of the first aspect of the present invention, the two-dimensional gas separation membrane comprises a layered double hydroxide gas separation membrane (LDH). As a type of two-dimensional nanomaterial, LDH has uniform interlayer channels, allowing accurate screening under the condition that the channel height is equivalent to the kinetic diameter of the guest molecule. Therefore, it shows good application prospects in gas membrane separation and is considered to be an ideal material for preparing high-performance gas separation membranes.
[0025] As a preferred embodiment of any technical solution of the first aspect of the present invention, the layered double hydroxide gas separation membrane is a MgAl-LDH membrane, which allows CO2 to pass through and retains N2. A typical LDH is a magnesium aluminum carbonate type hydrotalcite: Mg6Al2(OH) 16 CO3·4H2O. Preferably, the MgAl-LDH film is prepared by using a single MgAl-LDH nanosheet with a lateral size of more than 1 μm and a thickness of less than 5 nm.
[0026] As a preferred embodiment of any technical solution of the first aspect of the present invention, the method for preparing the MgAl-LDH film comprises the following steps:
[0027] Preparation of MgAl-LDH nanosheets;
[0028] A single layer or a few layers of MgAl-LDH nanosheets are peeled off; the peeled MgAl-LDH nanosheets are generally single layers or a few layers of MgAl-LDH nanosheets, and generally have a thickness of less than 5 nm, preferably less than 3 nm, which can be called single layers or a few layers of MgAl-LDH nanosheets. The single layers or a few layers of MgAl-LDH nanosheets are used for preparing MgAl-LDH films in the next step;
[0029] Preparation of MgAl-LDH membrane.
[0030] As a preferred embodiment of any technical solution of the first aspect of the present invention, the thickness of the MgAl-LDH film is greater than or equal to 1 μm. The MgAl-LDH film with a thickness of more than 1 μm will not cause breakdown after being sprayed with gold-plated electrodes, and can be successfully used for dielectric relaxation spectrum testing, and further accurately judge its relative selectivity for separating CO2 in CO2 / N2 mixed gas based on the results of the dielectric relaxation spectrum. When the thickness of the MgAl-LDH film is less than 1 μm, it is easy to break down after being sprayed with gold-plated electrodes, and it is impossible to further accurately judge its relative selectivity for separating CO2 in CO2 / N2 mixed gas based on the results of the dielectric relaxation spectrum.
[0031] As a preferred embodiment of any technical solution of the first aspect of the present invention, the relative air humidity refers to RH0% to 100%, including or excluding 0%. Preferably, RH is 30% to 90%. In the embodiment of the present invention, the selectivity of CO2 in CO2 / N2 mixed gas of MgAl-LDH membrane under RH of 30% to 90% is verified, and the measured selectivity is positively correlated with the dielectric relaxation of MgAl-LDH membrane measured by dielectric spectroscopy; for the same MgAl-LDH membrane, when the relative air humidity is greater, the characteristic dielectric relaxation time τ value of the gas separation membrane is greater, and the selectivity of CO2 in CO2 / N2 mixed gas of the gas separation membrane is greater (higher); when the relative air humidity of the MgAl-LDH membrane is smaller, the characteristic dielectric relaxation time τ value of the gas separation membrane is smaller, and the selectivity of CO2 in CO2 / N2 mixed gas of the gas separation membrane is smaller (lower). It should be noted that when the method of the present invention is used for judgment, the thickness of the MgAl-LDH membrane shall not be less than 1 μm; and when the selectivity of CO2 in the CO2 / N2 mixed gas is measured, the thickness of the MgAl-LDH membrane is generally not more than 100 nm. When the thickness of the MgAl-LDH membrane is too large during measurement, it will affect the permeability of the gas separation membrane, and the gas will not pass easily. Although the thickness of the MgAl-LDH membrane predicted by the dielectric relaxation spectrum is inconsistent with the thickness of the membrane measured for gas separation, since the dielectric relaxation spectrum reflects the viscosity of confined water under different relative humidity conditions, the difference in thickness does not affect the prediction result.
[0032] As a preferred embodiment of any technical solution of the first aspect of the present invention, the partial pressure of CO2 in the CO2 / N2 mixed gas is 0 to 10 bar, preferably 0 to 1 bar or 1 to 9 bar, excluding 0. The dielectric relaxation spectrum data show that as the partial pressure of CO2 in the CO2 / N2 mixed gas increases, the Debye relaxation peak gradually moves toward the low frequency direction, and accordingly, the dielectric relaxation time τ value gradually increases; that is, when the partial pressure of CO2 in the CO2 / N2 mixed gas is large, the selectivity of the MgAl-LDH membrane to CO2 in the CO2 / N2 mixed gas is improved.
[0033] As a preferred embodiment of any technical solution of the first aspect of the present invention, the applicable temperature is 273K to 373K, excluding the endpoint value. Preferably, the applicable temperature is 273 to 313K, excluding 273K; most preferably, the applicable temperature is 298 to 313K. The dielectric relaxation spectrum data show that when the temperature increases from 298K to 318K, the Debye relaxation peak shifts to a higher frequency direction, and the confined water exhibits a faster relaxation; that is, when the ambient temperature is higher, the MgAl-LDH membrane has a higher selectivity for CO2 in a CO2 / N2 mixed gas.
[0034] As a preferred embodiment of any technical solution of the first aspect of the present invention, when the τ value is equal to τ0, it is judged that the selectivity of the two-dimensional separation membrane to CO2 in the CO2 / N2 mixed gas is the same as that of the reference membrane.
[0035] The second aspect of the present invention provides a device for implementing the method of using dielectric spectroscopy to determine the selectivity of a gas separation membrane according to the first aspect of the present invention, comprising:
[0036] A MgAl-LDH two-dimensional gas separation membrane, wherein the thickness of the MgAl-LDH gas separation membrane is greater than or equal to 1 μm;
[0037] A first electrode, the first electrode covering one side of the MgAl-LDH two-dimensional gas separation membrane;
[0038] a second electrode, the second electrode covering the other side of the MgAl-LDH two-dimensional gas separation membrane parallel to the first electrode;
[0039] The first electrode and the second electrode are gold electrodes.
[0040] Preferably, the thickness of the first electrode and the second electrode is generally between 10 and 50 nm. When the thickness is less than 10 nm, the electrode will have discontinuous conduction, and when the thickness exceeds 50 nm, the gold electrode will block all gases, affecting the test results.
[0041] 3. Beneficial effects
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The present invention is the first to discover the correlation between the selectivity of CO2 in a CO2 / N2 mixed gas and the dielectric relaxation of a two-dimensional gas separation membrane; the method of the present invention measures dielectric relaxation by dielectric spectroscopy, and accurately predicts the selectivity of CO2 of a two-dimensional gas separation membrane in separating a CO2 / N2 mixed gas under different relative air humidity conditions by the change in dielectric relaxation (relative dielectric relaxation time), and experimentally verifies the selectivity of the gas separation membrane for CO2 in a CO2 / N2 mixed gas under different relative air humidity conditions, providing technical support for the research on efficient separation of two-dimensional gas separation membranes;
[0044] (2) The present invention takes the MgAl-LDH membrane that allows CO2 to pass through and retains N2 as an example, and uses the dielectric spectroscopy method to predict the CO2 selectivity of the MgAl-LDH membrane under different relative air humidity conditions, and conducts experimental verification. The verification results show that the dielectric spectroscopy prediction is consistent with the experimental results. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1(a) AFM of MgAl-LDH nanosheets; (b) SEM image of the top of the LDH film, scale bar is 10 μm; (c) SEM image of the cross-section of the LDH film, scale bar is 10 μm; the inset shows a photograph of the device used for dielectric measurements; (d). SEM image of the MgAl-LDH-HPAN film with a MgAl-LDH film thickness of approximately 100 nm, scale bar is 1 μm.
[0046] Figure 2 Schematic diagram of the dielectric relaxation performance measurement process.
[0047] Figure 3 (a) Dielectric relaxation spectra of MgAl-LDH film at 90% relative humidity, dry air and ethanol atmosphere; (b) Dielectric relaxation spectra of MgAl-LDH film at different relative humidity (30%, 60% and 90%) at 298K; (c) Variation of dielectric relaxation time and confined water viscosity with relative humidity; (d) Water absorption rate of MgAl-LDH film under different relative humidity conditions.
[0048] Figure 4 (a) Dielectric spectra of MgAl-LDH films at different relative temperatures when RH=90%; (b) Dielectric relaxation time and confined water viscosity change with relative humidity.
[0049] Figure 5 (a) and (b) are dielectric spectra of MgAl-LDH films under different CO2 pressures (RH90%, temperature 298K); (c) dielectric relaxation time and confined water viscosity change with relative CO2 pressure; (d) reversibility of dielectric relaxation in CO2 atmosphere, where pristine represents the original (0 bar CO2) and reverse represents the restored (0 bar CO2).
[0050] Figure 6 (a) Dielectric spectra of MgAl-LDH film at different temperatures under 1 bar CO2 pressure; (b) Temperature dependence of dielectric relaxation time (τ) of pristine MgAl-LDH and MgAl-LDH under 1 bar CO2 atmosphere fitted by Eyring model; (c) Temperature dependence of electrical conductivity of pristine MgAl-LDH and MgAl-LDH under 1 bar CO2 atmosphere.
[0051] Figure 7(a) Dependence of sodium carbonate concentration on relaxation time (τ) of sodium carbonate intercalated MgAl-LDH film at different relative humidity; red, green and blue star points represent the relative humidity dependence of relaxation time of MgAl-LDH film at 1, 5 and 9 bar CO2, respectively; the ordinate of the intersection of the two curves corresponds to the sodium carbonate concentration equivalent to the dissolution of carbon dioxide; (b) Equivalent carbonate concentration of MgAl-LDH film at different CO2 pressures; (c) Relative humidity dependence of relaxation time (τ) and viscosity (η) of sodium carbonate intercalated MgAl-LDH film; (d) Relative humidity dependence of pristine MgAl-LDH film and MgAl-LDH film at 1 bar CO2. Dielectric spectra of MgAl-LDH membranes immersed in different concentrations of sodium carbonate at 90% relative humidity under CO2 atmosphere; (e) Schematic diagram of CO2 ionization mechanism; (f) Simulation of the effect of interlayer anions on the electric field strength within the MgAl-LDH layer; (g) Structural geometry of enclosed water in MgAl-LDH membranes with 0 and 1 M carbonate embedded at different times under an external electric field of 10 V / nm and after exiting the electric field.
[0052] Figure 8 (a) Schematic diagram of the molecular structure of the MgAl-LDH nanochannel; the cyan, pink, red, white and blue balls represent Mg, Al, O, H and N atoms. The water molecules in the nanochannel are depicted as blue semi-transparent areas, and the blue line represents the boundary of the simulation box; (b) and (c) are molecular dynamics simulations of dielectric relaxation of pressurized water in the MgAl-LDH film; (b) 0M and (c) 1MNa2CO3 intercalated LDH channel dipole moment distribution simulation; (d) The system dipole moment decay curve after the external field of 10V / nm is drawn according to equation (6); (e) The dependence of the simulated lifetime (τ) of dipole relaxation on the concentration of intercalated Na2CO3.
[0053] Fig. 9 (a) Schematic diagram of the gas separation device, CH4 is the purge gas, MFC stands for mass flow meter, and GC stands for liquid chromatograph; (b) CO2 / N2 mixed separation performance of LDH membrane under different relative humidity. DETAILED DESCRIPTION
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0055] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0056] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.
[0057] Relative air humidity, temperature, thickness, amount and other numerical data can be presented in range format herein.It should be understood that such range format is used only for convenience and brevity, and should be flexibly interpreted as not only including the numerical value clearly described as the range limit, but also including all individual numerical values or sub-ranges included in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including individual numbers (such as 2,3,4) and sub-ranges (such as 1 to 3, 2 to 4, etc.).The same principle is applicable to the range of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values and ranges.In addition, no matter how the breadth of the described range or feature is, this interpretation should be applied.
[0058] If the relative air humidity is not clearly stated in the implementation mode, it is assumed to be RH90% by default; if the temperature is not clearly stated in the implementation mode, it is assumed to be 298 K by default. The present invention is further described below in conjunction with specific implementation modes.
[0059] Experimental Section
[0060] 1. Materials
[0061] Mg(NO3)2·6H2O (purity > 99%) and NaNO3 (purity > 99%) were purchased from Tianjin Damao Chemical Reagent Factory, China. Hexamethylenetetramine (HMT) (purity > 99.5%) was purchased from Beijing Inno Technology Co., Ltd., China. Al(NO3)3·9H2O (purity > 99%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., China. Na2CO3 was purchased from Shanghai Fuchen Chemical Co., Ltd., China. Polyacrylonitrile (PAN) ultrafiltration porous membrane with a molecular weight cutoff of 100,000 was purchased from Shanghai Meijia Vision Membrane Engineering Technology Co., Ltd., China. All chemicals were used directly without further purification.
[0062] 2. Preparation of gas separation membranes
[0063] Based on the principle of the present invention, the present invention uses dielectric spectroscopy to judge the selectivity of the gas separation membrane suitable for the layered double hydroxide gas separation membrane having the function of separating CO2 from the CO2 / N2 mixed gas.
[0064] The specific layered double hydroxide gas separation membrane in the embodiment is a MgAl-LDH membrane, and the preparation steps are as follows:
[0065] 1. Synthesis of MgAl-LDH nanosheets
[0066] MgAl-LDH nanosheets can be synthesized by a common method in the literature. Specifically, MgAl-LDH nanosheets are synthesized by a hydrothermal method: 20 mmol of Mg(NO3)2·6H2O, 10 mmol of Al(NO3)3·9H2O and 26 mmol of hexamethylenetetramine (HMT) are dissolved in 80 mL of deionized water, and the mixture is placed in an autoclave and heated at 140°C for 24 hours. The obtained white precipitate is washed repeatedly by centrifugation with water and ethanol (10,000 rpm) and then dried naturally at room temperature.
[0067] 2. Exfoliation of MgAl-LDH nanosheets
[0068] MgAl-LDH nanosheets can be exfoliated using a common method in the literature. Specifically, the sodium nitrate intercalation method is used to exfoliate the MgAl-LDH nanosheets: 0.3g of MgAl-LDH nanosheets are added to a mixed hydrochloric acid solution containing 300mL of 15M NaNO3 and 5mM HNO3. The mixture is shaken at a speed of 160rpm for 1 day under a N2 atmosphere to obtain MgAl-NO3 LDH nanosheets, which are then washed with water and ethanol, centrifuged, and dried. Then 0.1g of the nanosheets are added to 100mL of formamide, and the reaction is continued at a speed of 160rpm under a N2 atmosphere for 2 days to further exfoliate the MgAl-NO3 LDH nanosheets, and the unexfoliated particles are removed by centrifugation (2000rpm), and finally the fully exfoliated and formamide-dispersed MgAl-LDH nanosheets are obtained. Under this condition, the exfoliated MgAl-LDH nanosheets are monolayer or few layers with a thickness of less than 5nm.
[0069] 3. Preparation of MgAl-LDH two-dimensional layered membranes and carbonate intercalated MgAl-LDH membranes
[0070] The general method in the literature can be used to prepare MgAl-LDH two-dimensional layered membranes and carbonate-intercalated MgAl-LDH membranes. Specifically, a formamide-dispersed MgAl-LDH nanosheet solution is vacuum filtered on a Whatman Anodisc alumina ceramic substrate (pore size 0.2 μm, diameter 25 mm), and then peeled off to prepare a MgAl-LDH self-supporting layered membrane with a thickness of about 10 μm. The membrane is used to prepare a device for testing dielectric spectra and to perform dielectric relaxation spectrum tests.
[0071] The device for implementing the method of using dielectric spectroscopy to judge the selectivity of a gas separation membrane of the present invention may include the following structure:
[0072] MgAl-LDH two-dimensional gas separation membrane, thickness greater than or equal to 1 μm;
[0073] A first electrode covering one side of the MgAl-LDH two-dimensional gas separation membrane;
[0074] A second electrode covering the other side of the MgAl-LDH two-dimensional gas separation membrane parallel to and opposite to the first electrode;
[0075] The first electrode and the second electrode are gold electrodes.
[0076] For example, in an embodiment of the present invention, the above-mentioned 10 μm MgAl-LDH self-supporting layered membrane is used as a MgAl-LDH two-dimensional gas separation membrane, and a gold layer with a thickness of about 10 nm is sprayed on both sides of the membrane as the first electrode and the second electrode.
[0077] It should be noted that since the dielectric relaxation spectrum test requires gold-plated electrodes to be sprayed on both sides of the MgAl-LDH self-supporting layered film, if the thickness of the MgAl-LDH self-supporting layered film is too small, for example, 100nm, it will cause breakdown and the dielectric relaxation spectrum test cannot be performed. Experiments have shown that the MgAl-LDH self-supporting layered film with a thickness of more than 1μm will not cause breakdown after being sprayed with gold-plated electrodes, and can be successfully used for dielectric relaxation spectrum testing, and further accurately judge its relative selectivity for separating CO2 in CO2 / N2 mixed gas based on the results of dielectric relaxation spectrum. The thickness of the gold electrode is generally between 10 and 50nm. When the thickness is less than 10nm, the electrode will have discontinuous conduction, and when it exceeds 50nm, the gold electrode will block all gases, affecting the test results.
[0078] The original MgAl-LDH film was immersed in a series of concentrations (1×10 -4 ~1M) Na2CO3 solution for 8 hours. Then, the residual Na2CO3 solution on the surface was removed with deionized water and naturally air-dried at room temperature to obtain a carbonate-intercalated MgAl-LDH membrane.
[0079] 4. Preparation of MgAl-LDH-HPAN membrane for CO2 / N2 separation
[0080] The PAN substrate was pretreated with 2M NaOH for 1 hour to obtain a carboxyl functionalized hydrolyzed PAN (HPAN) substrate. The MgAl-LDH formamide dispersion was spin-coated onto the HPAN substrate at a speed of 2500 rpm to prepare a MgAl-LDH-HPAN membrane with a thickness of about 100 nm, which was used to measure the separation of CO2 in a CO2 / N2 mixed gas.
[0081] 3. Characterization of Gas Separation Membranes
[0082] 1. AFM of MgAl-LDH nanosheets:
[0083] like Figure 1 (a) shows an AFM image of the MgAl-LDH nanosheets peeled off in Part 2 of [II. Preparation of gas separation membranes]. The thickness of the MgAl-LDH flakes is about 3 nm, indicating that we have prepared MgAl-LDH nanosheets with fewer layers.
[0084] 2. 10μm MgAl-LDH self-supporting layered film:
[0085] like Figure 1 (b, c) are SEM images of the MgAl-LDH self-supporting layered membrane prepared in Part 3 of [II. Preparation of gas separation membrane], and the membrane thickness is about 10 μm.
[0086] 3. SEM of MgAl-LDH-HPAN film with a thickness of about 100 nm:
[0087] like Figure 1 (d) shows a cross section of a partially HPAN-supported MgAl-LDH membrane prepared in Part 4 of [II. Preparation of gas separation membranes].
[0088] 4. Preparation of dielectric test equipment
[0089] We sandwiched the MgAl-LDH self-supporting membrane (thickness of about 10 μm) prepared in Part 3 of [II. Preparation of gas separation membranes] between two 10 nm thick gold electrodes (SEM and appearance as shown in Figure 1 b inset), and a MgAl-LDH membrane device for dielectric relaxation spectrum test was obtained, wherein PET is polyethylene terephthalate (support template); the state of confined water inside the two-dimensional membrane was regulated by adjusting the humidity and temperature of the constant temperature and humidity chamber, and an impedance analyzer was used to measure and obtain dielectric spectrum data (schematic diagram as shown in Figure 2 ).
[0090] 5. Dielectric relaxation spectrum test
[0091] 1. Dielectric relaxation principle
[0092] As a characterization technique that is sensitive to changes in temperature, dipole number, dielectric environment, etc., dielectric spectroscopy can detect the dynamic characteristics of dipole relaxation by analyzing the phase and amplitude of the output signal under AC stimulation. In a typical dielectric spectrum, the complex dielectric constant ε^(ω) can be described by the Havriliak-Negami relaxation model:
[0093]
[0094] Where ε′ (dielectric constant) and ε″ (dielectric loss factor) represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ Represents ε′ at infinite frequency; Δε represents the relaxation intensity, which represents the difference between ε′ at zero and infinite frequency; τ represents the characteristic relaxation time; ω represents the frequency. When the temperature is constant, the τ value is positively correlated with the resistance to dipole rotation. The exponents α and β represent the skewness and broadening of the dielectric function, respectively, and their values range from 0 to 1; j represents different Havriliak-Negami terms when there are multiple relaxation processes. In addition, the viscosity changes in the two-dimensional confined channel caused by the limitation of the environment (such as polar solvents, charged nanopores, etc.) can be described by the dielectric spectrum according to the Debye model. The relationship between the dielectric relaxation time (τ) and the viscosity (η) in the confined space is:
[0095]
[0096] Where τ represents the characteristic relaxation time, k and T represent the Boltzmann constant and temperature respectively; a R represents the radius of the dipole molecule; η represents the viscosity.
[0097] 2. Dielectric spectrum measurement
[0098] All dielectric spectrum (also referred to as dielectric relaxation spectrum) measurement results in the present invention are obtained using an MFIA impedance analyzer from Zurich, controlled by LabOne software.
[0099] The dielectric spectrum was measured using an MFIA 5MHz impedance analyzer: Then the MgAl-LDH film device prepared in [IV. Preparation of dielectric test device] was connected to the impedance analyzer using wires. The measurement was performed in the frequency range of 0.01 to 5MHz, and the impedance value was converted into the dielectric constant using equation (7):
[0100]
[0101] Where l is the film thickness, A is the film area, i is the imaginary unit, ω = 2πf is the angular frequency, and e0 is the dielectric constant of free space (8.854×10 -12 F / m), Z* is the impedance value, and ε* is the dielectric constant.
[0102] For the tests in air environment, the temperature (T, 278-313K) and relative humidity (RH, 30-90%) were controlled by an environmental test chamber (DHTH-100-70-P-SD) with an accuracy of ΔT = 0.5°C and ΔRH = 1%.
[0103] For the tests under 0-1 bar and 1-9 bar CO2 pressure, CO2 and water vapor (30-90% RH) were introduced into a pressure-resistant stainless steel container (the membrane device was in a pressure-resistant stainless steel container). The CO2 pressure and RH were monitored by a manometer and SHTC3 humidity sensor, respectively, with an accuracy of 0.04 bar, 0.2 bar and 2%, respectively.
[0104] For the CO2 / N2 mixed gas test, CO2, N2 and water vapor (30-90% RH) were introduced into a pressure-resistant stainless steel container (the membrane device was in a pressure-resistant stainless steel container). The CO2 pressure, N2 pressure and RH were monitored by a pressure gauge and SHTC3 humidity sensor, respectively.
[0105] Before conducting the dielectric relaxation spectrum test, the film needs to be stabilized in the corresponding environment for 4 hours.
[0106] 6. Test of dielectric relaxation spectrum of gas separation membrane under different air humidity conditions
[0107] like Figure 3 As shown in a, under dry conditions, the dielectric spectrum of the MgAl-LDH film shows broadening and attenuation only below 1 Hz, which is consistent with the results reported previously. On the contrary, under humid conditions, the dielectric spectrum of the MgAl-LDH film shows a Debye peak in the range of 1 to 1000 Hz (as shown in Figure 3 a), and when the humidity is replaced by ethanol, the peak disappears (e.g. Figure 3 a). The appearance of the Debye peak in the range of 1-1000 Hz can be attributed to the presence of confined water in the interface channel of the MgAl-LDH layered structure. Because it is different from the dielectric relaxation of bulk water at frequencies greater than 17 THz, the relaxation process of confined water is significantly slower due to the spatial confinement of the two-dimensional channel. Therefore, by analyzing the dynamic relaxation process corresponding to the Debye peak in the range of 1-1000 Hz of the dielectric relaxation spectrum, it is possible for us to explore the influence of confined space on the motion state of water molecules.
[0108] In order to further explore the relationship between confined space and water molecule relaxation, the dielectric relaxation spectra of MgAl-LDH films at different relative humidity (RH) were studied. Figure 3 b and 3c). The results show that as RH increases from 30% to 90%, the relaxation time (τ) decreases exponentially, indicating that the rotational resistance of confined water decreases. According to formula (2), the viscosity of confined water increases from 1.31×10 4 Reduced to 2.46×10 3 Pa / s. In addition, Figure 3d further demonstrated that the content of adsorbed water increases with increasing RH (30% to 90%), and correspondingly, the channel size increases linearly from 0.86 nm to 1.13 nm. Therefore, the relaxation acceleration process caused by the increase in RH is essentially attributed to the decrease in viscosity, which is affected by the number of confined water molecules and their degree of confinement in the two-dimensional channel.
[0109] VII. Test of dielectric relaxation spectrum of gas separation membrane under different temperature conditions
[0110] In order to further explore the thermodynamic properties of dielectric relaxation in confined space, the temperature dependence of the dielectric properties of MgAl-LDH film was studied at 90% relative humidity. Figure 4 As shown in a. When the temperature increases from 298K to 318K, the Debye relaxation peak shifts to a higher frequency direction, and the confined water exhibits a faster relaxation ( Figure 4 b). Similar to the accelerated dielectric relaxation at high humidity, the faster relaxation at higher temperatures can also be attributed to the reduction in viscosity. Considering that the energy barrier associated with the polarization process is equal to the molar activation free energy (ΔF = ΔH - TΔS), according to the Erying chemical reaction kinetics theory, the relationship between relaxation time and temperature can be simplified to:
[0111]
[0112] Where h represents Planck's constant, k represents Boltzmann's constant, ΔH and ΔS represent the activation enthalpy change and activation entropy change during the relaxation process, respectively, and R represents the gas constant.
[0113] The experimental results are consistent with equation (3), and the increase in temperature leads to a decrease in the τ value. By fitting ln(τT) relative to 1 / T, we obtain the enthalpy change (ΔH) and entropy change (ΔS) of the relaxation process to be 34.1 kJ / mol and -13.3 J / mol / K, respectively (Table 1). It is worth noting that the ΔH value of confined water is 98% higher than that of bulk water (17.2 kJ / mol). Based on the ΔH value, we can calculate the average number of rearranged hydrogen bonds during dielectric relaxation according to equation (4):
[0114]
[0115] Where ΔH h-bonding Represents the strength of hydrogen bonds in pure water (10.9±0.4 kJ / mol).
[0116] The calculation shows that the number of hydrogen bonds of water confined between MgAl-LDH layers is 4.1, which is higher than 2.6 of bulk water, indicating that the strong dielectric environment is conducive to the expansion of dipole clusters, similar to the results of the water / ionic liquid mixed system reported previously. In addition, compared with bulk water (ΔS = 47.8 J / mol / K), the ΔS of the MgAl-LDH film is significantly reduced (-13.3 J / mol / K), which means that the confined water molecules can be polarized under the external electric field to form ordered clusters.
[0117] 8. Test of dielectric relaxation spectrum of CO2 selectivity of gas separation membrane for separation of CO2 / N2 mixed gas with different CO2 partial pressures
[0118] In order to investigate the role of confined water in the selective transport of CO2, the dielectric spectroscopy properties of MgAl-LDH membranes at 0-1 and 1-9 bar CO2 pressures were studied (e.g. Figure 5 a and Figure 5 b). Figure 5 As shown in a, at 298K, as the CO2 partial pressure increases from 0 to 1 bar, the Debye relaxation peak gradually moves toward the low frequency direction. Correspondingly, the τ value increases from 4.3×10 -3 s increases to 1.1×10 -2 s, the viscosity of the restricted water increases (e.g. Figure 5 c), indicating that the viscosity of water increases due to CO2 penetration, resulting in slower dielectric relaxation. In addition, the change in τ value caused by CO2 penetration is reversible (as shown in Figure 5 d).
[0119] IX. Test of dielectric relaxation spectra of CO2 selectivity of gas separation membranes for separation of CO2 from CO2 / N2 mixed gases with different CO2 partial pressures at different temperatures
[0120] On this basis, we studied the temperature dependence of the dielectric properties of MgAl-LDH films at 0 and 1 bar CO2 pressure (e.g. Figure 6 According to the Eyring model (Formula 3), by fitting ln(τT) and 1 / T (as shown in Figure 6 b), we calculated the ΔH and ΔS of the relaxation process under CO2 pressure (Table 1). Compared with the pure MgAl-LDH membrane, the introduction of CO2 leads to an increase of ΔH to 38.2 kJ mol -1 , indicating that the permeation of CO2 hinders the relaxation process of water molecule dipoles. In addition, the MgAl-LDH membrane permeated with 1 bar CO2 is 4.5, which is higher than that of pure MgAl-LDH membrane (4.1), indicating that confined water forms larger clusters around CO2 molecules. Compared with pure MgAl-LDH membrane, when CO2 permeates, ΔS is further reduced to -13.7 J / mol / K, indicating that there is an enhanced local electric field in the confined space. Therefore, the changes in activation enthalpy and entropy during CO2 permeation show similarities with the interaction between water and charged substances (such as ionic liquids, silicon-based materials, etc.).
[0121] Table 1. Thermodynamic parameters calculated by the Eyring model
[0122]
[0123] *Data cited from the literature Anomalous Debye-like dielectric relaxation of water in micro-sized confined polymeric systems. Phys. Chem. Chem. Phys. 15, 20153-20160 (2013); **Data cited from the literature Dielectric Anisotropy in Ice Ih. J. Phys. Soc. Jpn. 44, 1881-1886 (1978).
[0124] In addition, if Figure 6 As shown in Figure 3, under 1 bar CO2 pressure, the MgAl-LDH film exhibits higher conductivity than pure MgAl-LDH over the entire temperature range. Previously reported infrared spectroscopy studies have shown that there are signal peaks of carbonates between MgAl-LDH layers in a CO2 atmosphere. Therefore, the increase in conductivity can be attributed to the formation of carbonates due to the penetration of CO2.
[0125] 10. Principle of Dielectric Relaxation Spectroscopy Predicting CO2 Selectivity of Gas Separation Membranes for Separating CO2 / N2 Mixed Gases
[0126] In order to further evaluate the charged species generated during CO2 permeation and understand the effect of carbonate on dielectric relaxation, we used carbonate intercalated MgAl-LDH membrane to simulate the permeation and ionization process of CO2. -5 The pretreatment was carried out in sodium carbonate (Na2CO3) solution (1M to 1M) and the dielectric properties of MgAl-LDH films under different CO2 pressures and RH were compared. Figure 7 a) for comparison and quantitative analysis of the carbonate concentration that penetrates into the nanoconfined channel during CO2 transport ( Figure 7b) The results show that at 30-90% RH, as the concentration of the sodium carbonate pretreatment solution increases, the Debye relaxation peak region moves toward the lower frequency direction, and the dielectric relaxation time and viscosity of the confined water increase. It is worth noting that when the Na2CO3 concentration is close to 10 -3 M, the τ value is close to the τ value of 1bar CO2 permeating MgAl-LDH membrane. Figure 7 As shown in Figure 2b, the relationship between the increase of τ value and the increase of carbonate concentration can be described by the empirical formula (5):
[0127] lgτ=A[Na2CO3] k +B (5)
[0128] Where [Na2CO3] represents the concentration of Na2CO3, and A, B, and k are fitting parameters (see Appendix 2). By substituting the τ value and RH value of CO2 permeating the MgAl-LDH membrane into formula (5), we can estimate the amount of carbonate generated during CO2 permeation, as Figure 7 c shows that the carbonate concentrations generated by 1 bar CO2 permeation at 30% and 90% RH are close to 4×10 -4 and 4×10 -3 mol( Figure 7 The red triangle point in b) is 10 higher than the carbonate concentration produced in the bulk water at 1 bar CO2 penetration. 7 and 10 8 times. In addition, with the increase of CO2 pressure, the degree of CO2 ionization is further enhanced exponentially, which is also confirmed by the increase of τ value. Therefore, dielectric spectroscopy provides a visualization tool for characterizing the dissolution and ionization process of CO2 in two-dimensional confined channels. The ultrahigh viscosity caused by high van der Waals pressure in two-dimensional confined channels significantly promotes the ionization of CO2 in confined water. Under the promotion of confined water (RH = 90%) at 1 bar CO2 pressure, the degree of CO2 ionization of MgAl-LDH membrane increases by 8 orders of magnitude.
[0129] Table 2 Parameter fitting describing the relationship between relaxation time (τ) and carbonate concentration of MgAl-LDH membrane immersed in sodium carbonate
[0130]
[0131] The reversible ionization of CO2 with confined water promotes the selective transport of CO2. To gain a deeper understanding of the CO2-selective relaxation process of confined water, we studied the dielectric environment in the confined channel by finite element analysis. Figure 7Compared with the original MgAl-LDH based on nitrate, the local electric field around carbonate increases from 52 V / nm to 71 V / nm ( Figure 7 f), consistent with the increase in the viscosity of the confined water (2.47×10 4 ~1.60×10 5 Pa / s, such as Figure 7 b).
[0132] We also used molecular dynamics simulations to gain insight into the molecular motion mechanism of the dielectric relaxation process. In the pristine MgAl-LDH film (the simulation system of the MgAl-LDH nanochannel is shown in Figure 7 g), the dipole orientation of confined water is mainly aligned along the direction of the external electric field (10 V / nm) (as shown in Figure 8 a), exhibiting "electric freezing" behavior, as shown in ΔS (negative value) in Table 1. Then, 0.1ns after the external field is removed, the polarization orientation of the confined water becomes disordered, which is consistent with molecular polarization relaxation. The 1MNa2CO3 intercalated MgAl-LDH film also exhibits similar molecular polarization decay. However, in the transient state of the polarization relaxation process (such as 1ns), the degree of orientation order of water varies with the concentration of Na2CO3. Specifically, 1ns after the external field is removed, the dipole orientation of the confined water in the original MgAl-LDH is close to the fully relaxed state after 20ns ( Figure 8 b), while the confined water dipole orientation in the 1M Na2CO3 intercalated MgAl-LDH film is far from being completely relaxed ( Figure 8 c).
[0133] In order to quantitatively assess CO3 2- The dielectric relaxation depends on the system, and the empirical formula (6) is used to fit the decay of the system dipole moment γ(t). The results are as follows: Figure 8 d:
[0134]
[0135] Where t represents the transient time, τ0 represents the dipole relaxation lifetime, and 0<β≤1 is an exponential parameter.
[0136] The dipole relaxation lifetime (τ0) varies with the concentration of Na2CO3 as Figure 8 As shown in e. With the increase of Na2CO3 concentration, the dipole relaxation lifetime increases exponentially, indicating that the dielectric relaxation process is alleviated, which is consistent with our Figure 7 Therefore, the dielectric relaxation of confined water can provide direct evidence for studying the ionization of CO2 in separation membranes.
[0137] 11. Measured selectivity of gas separation membrane for separation of CO2 from CO2 / N2 mixed gas under different air humidity conditions
[0138] The ionization of CO2 in the presence of confined water in a two-dimensional confined channel provides an opportunity to design an efficient CO2 separation membrane. Based on CO2 separation, this study selected MgAl-LDH membrane and CO2 / N2 gas as the research model. The schematic diagram of the gas separation device is shown in Fig. 9 As shown in a. Fig. 9 As shown in Fig. 2a, the MgAl-LDH membrane exhibits extremely high CO2 and N2 permeabilities (3000-5000 GPU) under dry conditions, while the CO2 / N2 separation factor is almost negligible, indicating a near-leakage state. This can be attributed to the interlayer channel size (0.86 nm) of MgAl-LDH, which is much larger than the kinetic diameters of CO2 (0.33 nm) and N2 (0.36 nm). However, when the relative humidity of the feed gas mixture increases to 30%, the separation factor increases slightly to 3 accompanied by a significant decrease in permeability. It is worth noting that when the feed gas is at a relative humidity of 90%, the separation factor of the LDH membrane increases to 70 while maintaining a relatively high CO2 permeability (65 GPU), which exceeds most of the CO2 / N2 separation two-dimensional membranes in the prior art. Under humidity-activated conditions, the confined water between the MgAl-LDH layers promotes the entry of CO2 molecules into the interlayer nanochannels and ionizes them into CO3 2- , which plays a key role in achieving CO2 selective transport. Therefore, by introducing confined water into the confined space as a selective transmission channel to enhance the CO2 ionization effect, it is expected to achieve a breakthrough in the game effect between permeability and selectivity, and will also inspire the development and utilization of other two-dimensional layered membranes for precise and efficient molecular sieving.
[0139] In summary, this application developed a method for in-situ dielectric research and explored the mechanism of CO2 selective separation based on LDH layered membranes. By tracking the dielectric relaxation dynamics of confined water, the state of CO2 molecules was detected in situ and its reversible ionization process in a two-dimensional confined channel was revealed. The delayed dielectric relaxation process of confined water shows that CO2 ionization produces carbonates. By comparing the effects of CO2 ionization and Na2CO3 intercalation on dielectric relaxation, we found that the concentration of carbonates formed by CO2 ionization at 1 bar pressure in the MgAl-LDH membrane is 8 orders of magnitude higher than that of carbonates formed in bulk water, and the ionization of CO2 can be further enhanced by increasing the amount of confined water and the external pressure. Compared with dry conditions, the enhanced ionization of CO2 in confined water under RH = 90% increased the CO2 / N2 selective separation factor by 43 times. Therefore, this study proposed a new strategy to improve the separation efficiency of two-dimensional gas separation membranes based on dielectric research on the existence and movement of confined water molecules in two-dimensional confined channels, providing new ideas for promoting the development of this field.
[0140] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.
Claims
1. A method for determining the selectivity of a gas separation membrane using dielectric spectroscopy, characterized in that: The gas separation membrane includes a two-dimensional gas separation membrane; Selectivity includes selectivity of CO2 in CO2 / N2 mixed gas; Methods include: S1 measures the dielectric spectrum of the two-dimensional gas separation membrane in the range of 0.01 to 5 MHz under different relative air humidities, obtains the dielectric relaxation frequency, and then calculates the dielectric relaxation time; the dielectric relaxation frequency is obtained by fitting the dielectric spectrum curve with the Havriliak-Negami equation; the Havriliak-Negami equation is: Where ε' and ε" represent the real and imaginary parts of the dielectric constant, respectively; ε ∞ is the value of ε' at infinite frequency, Δε represents the relaxation intensity, that is, ε' at zero frequency and infinite frequency ε ∞ The difference between them; τ is the characteristic dielectric relaxation time, ω represents the angular frequency; the parameters α and β are used to describe the skewness and broadening of the dielectric function, ranging from 0 to 1; j represents different Havriliak-Negami terms in multiple relaxation processes; S2 According to the dielectric relaxation time of the two-dimensional gas separation membrane under different relative air humidity, the selectivity of the two-dimensional separation membrane to CO2 in the CO2 / N2 mixed gas under different relative air humidity is judged: The two-dimensional gas separation membrane under any relative air humidity is used as a reference membrane, and the dielectric relaxation time of the reference membrane is τ0; the two-dimensional gas separation membrane under other relative air humidity is used as the two-dimensional gas separation membrane to be tested, and the dielectric relaxation time of the two-dimensional gas separation membrane to be tested is τ; When the τ value is greater than τ0, it is judged that the selectivity of the two-dimensional gas separation membrane to CO2 in the CO2 / N2 mixed gas is greater than that of the reference membrane; When the τ value is less than τ0, it is judged that the selectivity of the two-dimensional gas separation membrane to CO2 in the CO2 / N2 mixed gas is less than that of the reference membrane.
2. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The two-dimensional gas separation membrane includes a layered double hydroxide gas separation membrane.
3. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to claim 1, characterized in that: The layered double hydroxide gas separation membrane is a MgAl-LDH membrane, which allows CO 2 to permeate and intercepts N 2 .
4. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to claim 3, characterized in that: The preparation method of the MgAl-LDH film comprises the following steps: Preparation of MgAl-LDH nanosheets; Exfoliation of single-layer or few-layer MgAl-LDH nanosheets; Preparation of MgAl-LDH membrane.
5. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to claim 4, characterized in that: The thickness of the MgAl-LDH film is greater than or equal to 1 μm.
6. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to any one of claims 1 to 5, characterized in that: The relative air humidity refers to RH0% to 100%.
7. The method for determining the selectivity of a gas separation membrane by using dielectric spectroscopy according to claim 3, characterized in that: The partial pressure of CO2 in the CO2 / N2 mixed gas is 0 to 10 bar, excluding 0.
8. The method for determining the selectivity of a gas separation membrane by using dielectric spectroscopy according to claim 3, characterized in that: The applicable temperature is 273K to 373K, excluding the endpoint values.
9. The method for determining the selectivity of a gas separation membrane using dielectric spectroscopy according to claim 1, characterized in that: When the τ value is equal to τ0, it is judged that the selectivity of the two-dimensional separation membrane to CO2 in the CO2 / N2 mixed gas is the same as that of the reference membrane.
10. A device for implementing the method of using dielectric spectroscopy to judge the selectivity of a gas separation membrane according to claims 1 to 9, comprising: A MgAl-LDH two-dimensional gas separation membrane, wherein the thickness of the MgAl-LDH gas separation membrane is greater than or equal to 1 μm; A first electrode, the first electrode covering one side of the MgAl-LDH two-dimensional gas separation membrane; a second electrode, the second electrode covering the other side of the MgAl-LDH two-dimensional gas separation membrane parallel to the first electrode; The first electrode and the second electrode are gold electrodes.
Citation Information
Patent Citations
Preparation of polyvinylamine / polyaniline mixed matrix membranes used for separation of gas containing carbon dioxide
CN104801207A
Aerosol deposition-based sensor humidity sensing thin film detection method
CN109696460A
Preparation method of gas separation composite membrane with high-hydrotalcite-content skin layer
CN112495199A
Magnesium-aluminum hydrotalcite matrix membrane as well as preparation method and application thereof
CN116099381A
Mixed matrix membrane for gas separation and preparation method thereof
CN116272408A
Cited By
Method for predicting confinement mass transfer efficiency of two-dimensional separation membrane by adopting dielectric spectrum
CN119499883A
Method for predicting mass transfer efficiency of two-dimensional separation membrane by dielectric spectroscopy
CN119499883B